Comparative analyses of the organelle genomes in Jacaratiaspinosa (Caricaceae) - Zuo, Liping; Lin, Zhicong; Chen, Huiru; Pan, Jianling; Zhu, Sihui; Ming, Ray (Frontiers in Plant Science, 2026)
IntroductionJacaratia spinosa (Aubl.) A. DC. (J. spinosa) is an important member of the Caricaceae family, valued for its edible properties and potential for protease development. However, organelle genome resources for this species have not been publicly available.MethodsTo fill this gap, we applied a hybrid sequencing approach combining Illumina short reads and Nanopore long reads, and assembled the complete mitochondrial and chloroplast genomes of J. spinosa using established assembly pipelines, followed by comprehensive annotation and genomic feature analysis.ResultsThe circular mitochondrial genome spans 461,675 bp, and encodes 40 protein-coding genes (PCGs), 26 tRNA genes, and 3 rRNA genes. The complete chloroplast genome is 160,000 bp in length, comprising 84 PCGs, 37 tRNA genes, and 8 rRNA genes. Both genomes contain numerous repetitive sequences. Codon usage analysis revealed a preference for leucine and codons ending with A or U, and several non-canonical start and stop codons were corrected via RNA editing. We identified 34 homologous sequence fragments, indicating frequent intracellular gene transfer events between the mitochondrion and chloroplast. Phylogenetic analysis confirmed that J. spinosa is most closely related to C. papaya among the species included, forming a sister group. Synteny analysis revealed that while the chloroplast genome of J. spinosa is highly conserved, the mitochondrial genome exhibited high similarity but with notable structural rearrangements. Selection pressure analysis indicated that the mitochondrial genes ccmFN and rps19, as well as the chloroplast genes ycf2 and rps4, are under positive selection.DiscussionThese findings expand the organelle genome resources for Caricaceae and provide valuable molecular evidence for phylogenetic and evolutionary studies within the family.